KOMPETENSI SOSIAL GURU BK/KONSELOR SEKOLAH (STUDI DESKRIPTIF DI SMA NEGERI KOTA PADANG) - Efendi, Gusfar (Konselor, 2013)
Abstract social competence is one’s capability in communicating and intreraction in order to create good coordination with theenvirontment. The school counselors are expected to have a good term with the school environment whether it is inside or outside the school. However, based on the pre-observation, this is not really applicable. There are no good cooperation between the school counselors and the school environment. This study was conducted to describe the social competence of school counselors based on internal collaboration in the work place, the role in the organization and guidance activity and inter-professional collaboration. This study was categorized as quantitative-descriptive research. The subject of 71 school counselors at Senior High School in Padang with bachelor degree title in guidance and counseling major. The result of the study revealed that the social competence of the school counselors was considered good. Keyword: social competence, guidace and counseling teacher/school counselor